Identification of the Types and Abundance of Microplastics in Telescopium telescopium in the Coastal Waters of Karimun Island, Riau Islands Province - Yana, Tesya Desi; Amin, Bintal; Siregar, Yusni Ikhwan (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2021)
This research was carried out in March 2020 to identify the type and abundance of microplastics and the relationship between the abundance of microplastics and the size (weight and length) of Telescopium telescopium in the coastal waters of Karimun Island, Riau Islands Province. Tanjung Balai Karimun has densely populated settlements and has many tourist attractions, so it is suspected that a large amount of plastic used is wasted into marine waters and fragmented into microplastics. The method used in this research is the survey method. The results showed that the abundance of microplastics in T.telescopium ranged from 6.9 - 12 particles/individual. The types of microplastics found were fibre, film and fragments, with the dominant type being Fiber. The abundance of fibre type microplastics has a strong relationship with weight and a moderate to length relationship. The abundance of film and fragment microplastics had a weak relationship with weight and length.